Case study of failure analysis in thin film silicon solar cell. Issue 9 (August 2015) - Mello, D.; Ricciari, R.; Battaglia, A.; Foti, M.; Gerardi, C.
Abstract: Thin-film silicon modules are commonly produced by an alternating sequence of layer deposition and layer patterning steps, which lead to a monolithic series connected device. Most used process is laser scribing process that offers a high throughput and a small area loss. Tin oxide (SnO2 ) or zinc oxide (ZnO) are the most used front contact TCO in the superstrate configuration. ZnO presents better optical properties with respect to SnO2 and can be realized by low thermal and cost effective deposition processes. Electrical performance of our tandem thin film silicon cell deposited on ZnO front contact has shown higher shunt with respect with our reference process using SnO2 front contact, not explained only as difference between the two materials. In this work, a failure analysis process was followed in order to explain the origin of the difference. SEM, FIB and Auger electron spectroscopy were used in order to characterize the laser scribe that is known to be a possible cause of electrical deviation. We found residuals either on the bottom either on the later wall of P3 scribe that can explain the lowering shunt resistance and open circuit voltage observed into the electrical performances of the module. Highlights: Failure analysis process flow was applied at solar cell To find a possible cause of electrical deviation, SEM, FIB and AES were used in order to characterize the laser scribe. The residuals found on the P3 scribe could explain the lowering shunt resistance and open circuit voltage of the module.